A Mixed-Signal Embedded Platform for Automotive Sensor Conditioning. (17th January 2010) - Volpi Volpi, Emilio Emilio; Fanucci Fanucci, Luca Luca; Giambastiani Giambastiani, Adolfo Adolfo; Rocchi Rocchi, Alessandro Alessandro; D'Ascoli D'Ascoli, Francesco Francesco; Tonarelli Tonarelli, Marco Marco; Melani Melani, Massimiliano Massimiliano; Marino Marino, Corrado Corrado
Abstract : A mixed-signal embedded system called Intelligent Sensor InterFace (ISIF) suited to fast identify, trim, and verify an architecture to interface a given sensor is presented. This system has been developed according to a platform-based design approach, a methodology that has proved to be efficient for building complex mixed-signal embedded systems with short time-to-market. Such platform consists in a wide set of optimized high-performance analog, digital, and software intellectual property (IP) modules for various kinds of sensors. These IPs can be easily defined for fast prototyping of the interface circuit for the given sensor. Final ASIC implementation for the given sensor conditioning can be easily derived with reduced risk and short development time. Some case examples are presented to demonstrate the effectiveness and flexibility of this system.